(untitled) (Economic and Political Thought, 2017)
The article aims to analyse the FRG’s policy toward Russia at the turn of the century and to present its significance to Europe and the development of a new global order. Moreover, the author tries to answer many questions concerning premises of cooperation between Russia and Germany as well as the threats they pose to European and world peace and security, inter alia, whether there will not be another Rapallo and whether Russia and Germany will not try to play a dominant role in Europe. The main thesis of the paper is an assumption that a way to a new, probably multipolar global order is very long and that Germany, remembering its history and tragic experiences, will not return to its policy of cooperation with Russia, which aims to take control over Europe and divide it again. On the other hand, the author writes, cooperation between Germany and Russia is indispensible for the stabilisation of the situation in Europe and the development of a new democratic order in the world.